A review on integrative approaches in oncology: bridging ayurvedic medicine and modern cancer therapeutics - Jha, Sudhanshu Kumar; Singh, Neha; Shanker, Ozasvi R.; Antil, Ishika; Baghel, Jaydeep Singh; Huddar, Vittal; Tripathi, Richa (Frontiers in Natural Products, 2025)
BackgroundCommon malignancies such as breast, lung, colorectal, prostate, and stomach cancers significantly contribute to cancer related death worldwide. Although conventional therapies including chemotherapy, radiotherapy, immunotherapy, and targeted agents have substantially improved cancer outcomes, their effectiveness is often constrained by off-target toxicities, therapeutic resistance, and limited efficacy in advanced-stage disease.ObjectiveThis review explores the potential of Ayurvedic formulations and bioactive phytochemicals alongside modern cancer treatments to enhance the safety and efficacy of cancer therapies.MethodsThe review highlights recent advancements in both conventional and alternative cancer treatments, focusing on the pharmacological properties of Ayurvedic botanicals and their integration with modern oncology through translational research and precision medicine.ResultsAyurvedic plants like Phyllanthus emblica (Amalaki), Piper nigrum (Piperine), Withania somnifera (Ashwagandha) and Curcuma longa (Haridra) contain bioactive phytochemicals that exhibit anti-proliferative, pro-apoptotic, and anti-metastatic effects, effectively targeting key cancer hallmarks. These phytochemicals are integrated into evidence-based oncology through reverse pharmacology. Modern oncology complements this approach with immunotherapies like Pembrolizumab and CAR-T cell therapies, targeted therapies such as Bevacizumab and Dabrafenib, and precision medicines like Imatinib, Trastuzumab, and Osimertinib. Additionally, hormonal therapies, along with innovations like radiopharmaceuticals and PARP inhibitors, expand the range of therapeutic options.ConclusionIntegrating Ayurvedic phytochemicals with modern oncology provides a comprehensive framework for overcoming the limits of existing cancer treatments. This integrative approach enhances the safety, efficacy, and personalization of cancer medicines by combining conventional knowledge with new advances to generate creative cancer care.